Volume 9: Mechanical Systems and Control, Parts A, B, and C 2007
DOI: 10.1115/imece2007-42108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acoustic Noise on the Dynamic Performance of MEMS Gyroscopes

Abstract: Advances in MEMS technology have resulted in relatively low cost gyroscopes and accelerometers and, correspondingly, inexpensive inertial measurement systems. This has opened up the field of applications for inertial measurement units (IMUs) and they are currently being proposed for use in a wide variety of possible applications, with environmental conditions ranging from mild to harsh. Of particular interest in this study are MEMS gyroscopes, which are based upon vibratory, rather than rotational, designs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Motion sensors have been shown prone to acoustic noise particularly at high frequency and power level in [12], [13], [14], which showed that MEMS gyroscopes are susceptible to high power, high frequency noise that contains frequency components in proximity of the resonating frequency of the gyroscope's proof mass. This concept of work was further utilized by Son et al [15] to interfere with the flight control system of a drone using intentional sounds that were produced by a Bluetooth speaker attached to the drones with a sound pressure level of 113dB.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion sensors have been shown prone to acoustic noise particularly at high frequency and power level in [12], [13], [14], which showed that MEMS gyroscopes are susceptible to high power, high frequency noise that contains frequency components in proximity of the resonating frequency of the gyroscope's proof mass. This concept of work was further utilized by Son et al [15] to interfere with the flight control system of a drone using intentional sounds that were produced by a Bluetooth speaker attached to the drones with a sound pressure level of 113dB.…”
Section: Background and Related Workmentioning
confidence: 99%
“…All these results seem to indicate that direct acoustic vibrations are unable to affect the motion sensors while traveling through air. However, it is possible for other sounds such as high frequency audio signals to affect gyroscope and accelerometer as shown in [12], [13], [14], [15]. The difference lies in the frequencies and power levels of the audio signals used to influence the motion sensors.…”
Section: Summary and Further Insightsmentioning
confidence: 99%
“…However, Bayon et al [36], [49] targeted a more realistic TRNG composed of 50 ROs. frequency can degrade the performance of the sensor [126]- [128]. However, the security effects of intentional sound transmissions were not explored until the 2015 "Rocking Drones" paper by Son et al [10].…”
Section: Acoustic Emanationsmentioning
confidence: 99%
“…Intentionally altering sensor output using physical signals sources is a topic of recent research. Depending on the structure of a MEMS gyroscope, performance degradation can be induced by acoustic resonance [37], [38], [39], [17]. Moreover, researchers have used the data from gyroscopic sensors as a side channel to extract information [40], [41].…”
Section: Hard Drive Covert and Side Channelsmentioning
confidence: 99%